La gestión del talento humano en la institución pública: Sistema de evaluación del desempeño para las y los servidores de la dirección de agua potable y alcantarillado del Gobierno Autónomo Descentralizado Municipal de Rumiñahui, GGADMUR. - Ordoñez Chamba, Jorge Augusto (2014)
The Independent Government Decentralized Policeman of Rumiñahui, GADMUR, works to reach the objectives drawn up by the town hall, as well as to obtain the efficiency and effectiveness in the benefit of the services to the community. At the present time, the Direction of Human Talent of the GADMUR does not have a tool of management evaluation to the Potable Water Direction and Sewage system, instrument that contributes to the personal development and professional of and the servants, whom a suitable unfolding allows and the fulfillment of the institutional objectives is obtained; when not counting on this tool of management, it generates malaise between and the municipal servants, as well as in the users who go to this dependency to ask for the services. The methodology raised in the present investigation, took place with the purpose of giving concrete answers to the specific objectives, an instrument was designed whose objective was to receptar information and the technique of the survey was used. The benefits of the result of the investigation, will be reflected in the attitude of and the servants who serve their in the municipal institution, which they must orient his management towards the benefit of services of quality, with the application of his competitions, knowledge, abilities, skills, values and attitudes, in the fulfillment of their obligations and responsibilities. Like premise, the public service and the administrative race must like objective reach the professional and technical development of and the servants, to obtain the permanent improvement, efficiency, effectiveness, quality, productivity of the State and its institutions, by means of the conformation, operation and development of a system of management of the human talent, sustained in the equality of: rights, opportunities and the nondiscrimination.